Al-Rajul/Al-Wathan fi Syi’ri al-Marah al-Arabiyyah al-Mua’shirah 1975-2000 M (Ru’yah Naqdiyyah fi Dhau’ Manhaj al-Naqd al-Tsaqafiy) / Man/Homeland in Contemporary Arab Women’s Poetry 1975-2000 AD (A Critical Vision in Light of the Cultural Criticism Approach) - Awatef El Badri Mohamed Ata (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
The study aims to reveal the special cultural connotations in the textual structures that carry intellectual patterns with political and social implications, relying on the semantic focus in presenting the poetic content, which carries the meanings of the presence of the man/homeland in an indirect, suggestive way in the Egyptian women’s poem, and reading what is behind its lines from a social perspective concerned with By studying the literary text through its emotional transformation into expression with emotional and pictorial equivalents through a set of poetic tools and techniques - symbol, mask, and drawing inspiration from characters and events from human heritage, and religious heritage - and everything that adds strength and credibility to the text; To reveal the systemic - implicit - connotations and foundations of the relationship between the man and the nation within it, and to monitor its transformations due to the changes that occurred in society during the time period of the research (1975-2000 AD); with the aim of understanding its inner worlds, achieving the maximum degree of effectiveness and influence, and linking the literary phenomenon to the social reality in which it was created. To express through it, and to open broader contexts to the text than those imposed by the structural and stylistic school on the critical process with its uniqueness and unity of interpretation. This necessitated discussing contemporary women’s poetry in the Arab region during the research period, and then delving into revealing the cultural connotations of the manifestations of the image of man/homeland, its stylistic aesthetics in the poetry of Arab women in general, and Egyptian women in particular, and the extent of the intertwining and conflict between the vision of men and the homeland in their texts. And the cultural cognitive structure that was relied upon in its formation.المستخلص: تتوجه الدراسة إلى الكشف عن الدلالات الثقافية الخاصة في البنيات النصية الحاملة لأنساق فكرية ذات مضامين سياسية واجتماعية معتمدة على التركيز الدلالي في تقديم المضمون الشعري، الحامل لمعاني حضور الرجل/ الوطن بطريقة إيحائية غير مباشرة في القصيدة النسائية المصرية، وقراءة ما خلف سطورها من منظور اجتماعي يُعنى بدراسة النص الأدبي من خلال تحوله الانفعالي العاطفي إلى التعبير بالمعادل الشعوري والتصويري من خلال مجموعة من الأدوات والتقنيات الشعرية- الرمز والقناع واستلهام شخصيات وأحداث من التراث الإنساني، والموروث الديني- وكل مايضفي قوة ومصداقية على النص؛ لكشف الدلالات النسقية – المضمرة - وأسس العلاقة بين الرجل والوطن داخلها، ورصد تحولاتها بفعل التغيرات التي طرأت على المجتمع خلال الفترة الزمنية للبحث (1975-2000م)؛ بهدف فهم عوالمها الداخلية، وتحقيق أقصى درجة من الفاعلية والتأثير، وربط الظاهرة الأدبية بالواقع الاجتماعي الذي أُبدِعت في ظله؛ للتعبير من خلالها، وفتح سياقات أكثر رحابه على النص من تلك التي فرضتها المدرسة البنيوية والأسلوبية على العملية النقدية بالتفرد ووحدانية التفسير. وقد استلزم ذلك تناول الحديث عن الشعر النسائي المعاصر في المنطقة العربية خلال فترة البحث، ثم الولوج منها إلى كشف الدلالات الثقافية لتجليات صورة الرجل/ الوطن، وجمالياتها الأسلوبية في شعر المرأة العربية بصفة عامة، والمصرية خاصة، ومدى التشابك والتنازع بين رؤية الرجل والوطن في نصوصها، والبنية المعرفية الثقافية التي اتكأت عليها في تشكيلها.